A Case of Phenibut Withdrawal Management and Detoxification Using Baclofen in the Outpatient Setting - Emma DiFiore; Julie Pittman (Case Reports in Psychiatry)
Phenibut, a GABAB receptor agonist, has surged in popularity due to its nootropic and anxiolytic effects. Despite not being FDA approved, it is accessible online due to its marketing as a dietary supplement, leading to unregulated distribution. Increasing reports have highlighted the risks of addiction and severe withdrawal symptoms associated with phenibut use. This case report explores the management of phenibut withdrawal in an outpatient setting using a baclofen taper. The slow taper was complicated by various withdrawal symptoms, and the patient was ultimately stabilized on lorazepam, baclofen, gabapentin, and clonidine after 5-months time. This case is unique, as it also highlights challenges in tapering off baclofen following phenibut detoxification. The study underscores the need for further research on the pharmacological management of phenibut withdrawal, emphasizing the importance of raising awareness about phenibut’s dangers and associated clinical presentations.